Mutagenicity and antimutagenicity of hydrophilic and lipophilic extracts of Thai northern purple rice - Punvittayagul C. (Asian Pacific Organization for Cancer Prevention, 2015)
Purple rice (Oryza sativa L. var. indica) cv. Kum Doisaket is cultivated in northern Thailand. This study evaluated the mutagenic and antimutagenic properties of hydrophilic and lipophilic components of purple rice using the Ames test. The seed and hull of purple rice were extracted with hexane, methanol, ethanol, and water. The methanol extracts had the highest amounts of phenolic acids and flavonoids, while the hexane extracts contained large amount of tocols and γ-oryzanol. None of the extracts were mutagenic in Salmonella typhimurium strains TA98 and TA100. The hexane extract of rice hull and the methanol extract of rice seed were strongly effective against aflatoxin B1- and 2-amino-3, 4 dimethylimidazo (4, 5-f) quinoline-induced mutagenesis, while aqueous extracts showed weakly antimutagenic properties. All extracts with the exception of aqueous extracts enhanced the number of revertant colonies from benzo (a) pyrene induced-mutagenesis. None of the extracts inhibited mutagenesis induced by the direct mutagens 2-(2-furyl)-3-(5-nitro-2-furyl)-acrylamide and sodium azide. The hull extracts showed more potent antimutagenicity than the seed extracts. Based on a chemical analysis, γ-oryzanol and γ-tocotrienol in the hull and cyanidin-3-glucoside and peonidin-3-glucoside in the seed are candidate antimutagens in purple rice. The antimutagenic mechanisms of purple rice might be related to either modulation of mutagen metabolizing enzymes or direct attack on electrophiles. These findings supported the use of Thai purple rice as a cancer chemopreventive agent.